Comparative Serological Studies In Milk And Serum And Evaluation Of Efficacy Of Brucella Abortus S99 - Koppad, Sanganagouda; S.M, Byregowda; Murag, Shivaraj; Mayanna, Asha; G.K., Chandrakala; Sobharani ,; M.D. , Venkatesha (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was conducted to compare serological characteristics of milk and serum from brucellosis suspected cows. The serological tests like Rose Bengal Plate Test (RBPT), Milk Ring Test (MRT), Standard Tube Agglutination Test (STAT) and Enzyme Linked Immune Assay (ELISA) were conducted for the detection of antibodies in serum and milk and the results were compared. Hyper immune serum (HIS) against Brucella abortus S99 was raised in rabbits and was tested against RBPT and plain antigen by STAT. The HIS showed an antibody titre of 1: 2560.
Keywords: MRT; RBPT; ELISA; HIS; STAT